Perbandingan Indeks Massa Tubuh pada Siswa dan Siswi Konsumsi Ultra-Processed Food di SMA Xaverius 1 Jambi - Heri Yanto Putra; Alexander Halim Santoso (Universitas Malahayati Lampung, 2024)
ABSTRACT According to the World Health Organization's European Regional Obesity Report 2022, obesity is a complex multifactorial condition caused by excess adiposity and is linked to an elevated risk of noncommunicable diseases. Riskesdas Jambi Province in 2018 reported that 7.8% of adolescents were overweight and 2.7% were obese. Ultra-processed food undergoing extensive processing is considered obesogenic due to its high calorie, sugar, and salt content. This study aims to determine the mean difference of body mass index (BMI) among students who ate frequent and infrequent in Xaverius 1 senior high school students in Jambi City. This study was a cross-sectional design with a sample size of 143 students. Data collection was carried out using a consecutive sampling technique and were analyzed using Mann-Whitney. In this study, there was no significant difference in mean of body mass index between students who frequently consumed UPF and those who rarely consumed UPF (p0,05). Further researches are recommended with more precise method to see more association of risk factor toward obesity in adolescent. The difference in Mean Body Mass Index between Frequent and Infrequent Ultra Processed Food Consumption Groups was 0,68 (-0,76 – 2,12) points. Keywords: Ultra-Processed Food, Body Mass Index, Obesity, Adolescent ABSTRAK Menurut Laporan WHO European Regional Obesity 2022, obesitas adalah kondisi multifaktorial kompleks yang disebabkan oleh kelebihan adipositas dan terkait dengan peningkatan risiko penyakit tidak menular. Riskesdas Provinsi Jambi tahun 2018 melaporkan sebanyak 7,8% remaja gemuk (overweight) dan 2,7% remaja obesitas. Ultra-Processed Food adalah jenis makanan yang mengalami pengolahan ekstensif dan dianggap sebagai penyebab obesitas karena kandungan kalori, gula, dan garam yang tinggi. Penelitian ini bertujuan untuk mengetahui perbedaan rerata indeks massa tubuh (IMT) antara siswa yang sering dan yang jarang mengonsumsi Ultra-Processed Food pada siswa SMA Xaverius-1 Kota Jambi. Penelitian ini merupakan penelitian potong lintang dengan jumlah sampel sebanyak 143 responden. Pengumpulan data dilakukan dengan menggunakan teknik consecutive sampling dan dianalisis dengan menggunakan Mann-Whitney. Hasil penelitian ini menunjukkan bahwa tidak terdapat perbedaan rerata indeks massa tubuh yang bermakna antara siswa yang sering dan yang jarang mengonsumsi Ultra-Processed Food (p0,05). Penelitian lebih lanjut dengan metode yang lebih tepat disarankan untuk melihat lebih jauh hubungan faktor risiko terhadap obesitas pada remaja. Kata Kunci: Ultra-Processed Food, Indeks Massa Tubuh, Obesitas, Remaja